Optimalisasi Potensi Lokal Melalui Pembangunan Gapura Bambu oleh Masyarakat dan Mahasiswa KKN untuk Meningkatkan Identitas Desa Silatong, Kecamatan Simpang Kanan - Rehan, Rehan; Amiruddin, Amiruddin; Yufrizal, Yufrizal; Yusmanijar, Yusmanijar; Pasaribu, Jupita Sari; Agustina, Lia; Rohani, Rohani (Mitra Abdimas: Jurnal Pengabdian kepada Masyarakat, 2024)
The purpose of this study is to maximize and optimize local potential in Silatong Village, Simpang Kanan District, through more effective and efficient bamboo management. Bamboo was chosen because of its material ability to provide a strong structure and unique aesthetics. As a result, bamboo gates are used as a symbol of strong and environmentally friendly rural identity, with the aim of increasing community productivity in bamboo cultivation. The research method uses a participatory approach, which involves providing information to the public at every stage of project planning and implementation. Active participation of residents is very important in developing products that are relevant and useful for the local community. The results of making the gate show that local identity and active community participation play an important role in the development process. As a result, this project not only provides physical benefits such as infrastructure and production facilities, but also fosters a sense of togetherness and concern among fellow residents of Silatong Village. The results of this activity are expected to be an example for other communities in utilizing local resources effectively and efficiently.